Optimalisasi Media Sosial UMKM sebagai Alat untuk Memperluas Jangkauan Pasar “Kue Ali Kaum Lestari Bu Ina” - Indra Maulana; Kinara Septiana Indaswari; Nazia Annura; Fitriyani Siti Nurjanah; Radeeva Salsabila (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
Micro, Small, and Medium Enterprises (MSMEs) need to adapt to digital transformation in order to remain competitive amid changing modern consumer behavior. One strategy that can be applied is digital transformation through the use of marketing media that combine both offline and online methods. Kue Ali Kaum Lestari Bu Ina, a traditional culinary MSME in Purwakarta, still relies on word-of-mouth promotion and direct sales, resulting in slow market growth despite having a good local reputation. This community service activity aims to improve the understanding and skills of Micro, Small, and Medium Enterprises (MSMEs) Kue Ali Kaum Lestari Bu Ina regarding the importance of digital transformation strategies through optimizing social media to expand market reach and maintain customer loyalty. The initiative utilizes digital tools, human resources with digital content skills, and platforms such as Instagram, Tiktok and WhatsApp Business. The methods used are interviews and discussions as well as training and mentoring to guide business actors in creating business accounts and managing social media. The results show that the strategic use of social media can increase product visibility, and expand market reach.